The Effects of Profitability, Financial Risk and Corporate Growth on Profit Management on Healthcare Companies Listed on The Indonesian Stock Exchange Period 2018-2022 - Anggraini, Puput Diah; Imronudin, Imronudin (SENTRALISASI, 2024)
The purpose of this study is to analyze the impact on profitability, the risk of financial failure, and the growth of the corporate with regard to profit management in healthcare companies listed on the Indonesian Stock Exchange for the years 2018–2022. The population included in this study included thirty-two companies. In this study, 17 companies were sampled using the purposive sampling method. Documentation and case studies are the data collection methods used in this study. The type of data used is secondary data consisting of financial accounting records that are generated using the Eviews application tool. The results of the research indicate that while profitability has no significant effect on profit management. The variable of financial risk has a positive and significant effect on profit management. The corporate growth variable does not have a significant effect on profit management. Simultaneously the variables of profitability, financial risk and corporate growth have a significant influence on profit management. The Adjusted R-Squared value of 41.76% indicates the degree to which the variables of profitability, financial risk, and corporate growth influence profit management, with the remaining 58.24% being influenced by other factors.